Investigating the role of free-living amoebae as a reservoir for Mycobacterium ulcerans. - Nana Ama Amissah; Sophie Gryseels; Nicholas J Tobias; Bahram Ravadgar; Mitsuko Suzuki; Koen Vandelannoote; Lies Durnez; Herwig Leirs; Timothy P Stinear; Françoise Portaels; Anthony Ablordey; Miriam Eddyani (Public Library of Science (PLoS), 2014)
The reservoir and mode of transmission of Mycobacterium ulcerans, the causative agent of Buruli ulcer, still remain a mystery. It has been suggested that M. ulcerans persists with difficulty as a free-living organism due to its natural fragility and inability to withstand exposure to direct sunlight, and thus probably persists within a protective host environment.We investigated the role of free-living amoebae as a reservoir of M. ulcerans by screening the bacterium in free-living amoebae (FLA) cultures isolated from environmental specimens using real-time PCR. We also followed the survival of M. ulcerans expressing green fluorescence protein (GFP) in Acanthameoba castellanii by flow cytometry and observed the infected cells using confocal and transmission electron microscopy for four weeks in vitro. IS2404 was detected by quantitative PCR in 4.64% of FLA cultures isolated from water, biofilms, detritus and aerosols. While we could not isolate M. ulcerans, 23 other species of mycobacteria were cultivated from inside FLA and/or other phagocytic microorganisms. Laboratory experiments with GFP-expressing M. ulcerans in A. castellani trophozoites for 28 days indicated the bacteria did not replicate inside amoebae, but they could remain viable at low levels in cysts. Transmission electron microscopy of infected A. castellani confirmed the presence of bacteria within both trophozoite vacuoles and cysts. There was no correlation of BU notification rate with detection of the IS2404 in FLA (r = 0.07, n = 539, p = 0.127).This study shows that FLA in the environment are positive for the M. ulcerans insertion sequence IS2404. However, the detection frequency and signal strength of IS2404 positive amoabae was low and no link with the occurrence of BU was observed. We conclude that FLA may host M. ulcerans at low levels in the environment without being directly involved in the transmission to humans.